Characteristics of Paleotsunami Sediments, A Case Study in Cilacap and Pangandaran Coastal Areas, Jawa, Indonesia - Yudhicara, Yudhicara; Zaim, Y.; Rizal, Y.; Aswan, Aswan; Triyono, R.; Setiyono, U.; hartanto, D. (Geological Agency, 2013)
DOI:Â 10.17014/ijog.v8i4.166A paleotsunami study having been conducted in 2011 took two study cases in Cilacap and Pangandaran coastal areas. These two regions have been devastated by tsunami in the past and had the most severe damaged on 17 July 2006. Trenching, beach profiling, and sediment sampling had been carried out, and further analysis at the laboratory had been done, such as grain size and fossil analyses and dating. In Cilacap, an iron sand layer was found as a key bed suspected as a paleotsunami deposits due to the content of anthropogenic fragments. In Pangandaran, two layers of tsunami deposit candidates were found having thickness of 5 - 6 cm at the top as a 2006 tsunami deposit candidate, and 5 - 10 cm at the bottom as a paleotsunami deposit candidate. Both grain size and fossil analysis results could explain that Pangandaranâs sediments are tsunami deposits while Cilacapâs ones are assumed to be deposited by another process rather than a tsunami.